Information processing and management International Conference on Recent Trends in Business Administration and Information Processing, BAIP 2010, Trivandrum, Kerala, India, March 26-27, 2010. Proceedings - International Conference on Recent Trends in Business Administration and Information Processing (Communications in Computer and Information Science, 2010)
It is my pleasure to write the preface for Information Processing and Management. This book aims to bring together innovative results and new research trends in information processing, computer science and management engineering. If an information processing system is able to perform useful actions for an objective in a given domain, it is because the system knows something about that domain. The more knowledge it has, the more useful it can be to its users. Without that knowledge, the system itself is useless. In the information systems field, there is conceptual modeling for the activity that elicits and describes the general knowledge a particular information system needs to know. The main objective of conceptual modeling is to obtain that description, which is called a conceptual schema. Conceptual schemas are written in languages called conceptual modeling languages. Conceptual modeling is an important part of requiriments engineering, the first and most important phase in the development of an information system. SVD and neural network based watermarking scheme - Improved web precision: an interplay of proximity heuristics and semantic association of query-terms - Network management initialization for wired and wireless communication: a real time study - IMM-I46: Inter Mobility Management for an integrated IPv4 and IPv6 network - An efficient multicast hybrid routing protocol for MANETs - Applications of graph theory in face biometrics - Substitution-diffusion based image cipher using chaotic standard map and 3D cat map - Hybrid activities of AODV for wireless Ad hoc sensor network - Design and evaluation of a fuzzy-based CPU scheduling algorithm - Object location in cluster based mobile Ad Hoc networks - Performance analysis of coded OFDM for various modulation schemes in 802.11a based digital broadcast applications - Fast OVSF code assignment scheme for WCDMA wireless networks - A closed form slew evaluation approach using Burr’s distribution function for high speed on-chip RC interconnects - Wavelet-domain L??? - Constrained two-stage near-lossless EEG coder - Fuzzy based bandwidth management for wireless multimedia networks - A novel digital algorithm for sobel edge detection - Efficient intrusion detection with reduced dimension using data mining classification methods and their performance comparison - Recognition of isolated indian sign language Ggsture in real time - Power-efficient cache design using dual-edge clocking scheme in sun OpenSPARC T1 and Alpha AXP processors - Power consumption analysis of direct, set associative and phased set associative cache organizations in Alpha AXP 21064 processor - Role of resolution in noisy pattern matching - Integrating an efficient authorization protocol with trigon-based authentication mechanism for improving grid security - Bandwidth estimation scheme for mobile Adhoc network - Multimodal biometric invariant moment fusion authentication system Histogram equalization for class-identification dental disease using digital radiography - Comparison of histogram and spatiograms for content based retrieval of remote sensing images - Vector quantization for tumor demarcation of mammograms - Selective encryption of video using multiple chaotic maps - Optimizing the hybrid approach for time synchronization in wireless sensor networks - Tracking based secure AODV routing protocol - Study of visitor behavior by web usage mining - A hybrid routing protocol for wireless sensor network - Efficient group key distribution mechanism for dynamic groups using public key broadcast ring - Investigation on effectiveness of simulation results for wireless sensor networks - A novel multipath routing scheme in mobile Adhoc networks - A novel security approach for detecting black hole attack in MANET - NEEMON algorithm based on data locality for priority based dynamic load balancing in distributed database - A secure e-shopping using voice ordering - Performance analysis of all-optical WDM network with wavelength converter using erlang C traffic model - A concurrent synchronization model for distributed multimedia systems - Secure QoS enabled on-demand link-state multipath routing in MANETS - A novel approach for building a dynamically reconfigurable trustworthy distributed system - An improved three pattern huffman compression algorithm for medical images in telemedicine - Encryption algorithm for block ciphers based on programmable cellular automata - Performance analysis of reactive routing protocols with OSPF for IEEE 802.11s wireless mesh network - Quality of service on-demand power aware routing algorithm for wireless sensor networks - A cryptographic approach to defend against IP spoofing - Multi-agent based network performance tuning in grid - Finding discriminative weighted sub-graphs to identify software bugs Border gateway routing protocol convergence time analysis with minimum route advertisement information - Design and implementation automatic incorporation of corrections into reviewed documents - Performance comparison of multicast routing protocols for MANETs - Traffic aware LSP selection method in MPLS - Context-aware intrusion detection in mobile Ad-Hoc networks - Energy and fault aware management framework for wireless sensor network - An image index model for retrieval - Trust based strategy to resist collaborative blackhole attack in Manet - Extended finite state machine model-based regression test suite reduction using dynamic interaction patterns - Throughput analysis of HWMP routing protocol in wireless mesh networks - Separation of machine printed Roman and Gurmukhi script words - FPGA implementation of AES co-processor in counter mode - Detecting plagiarism in text documents - Hiding relevant information in an image - Knowledge discovery from web usage data: a survey of web usage pre-processing techniques - Context-aware system using.NET approach - genetic audio watermarking - Effective BST approach to find underflow condition in interval trees using augmented data structure - Natural disaster impact assessment using genetic algorithm - An approach to enhance security environment based on SIFT feature extraction and matching to iris recognition - A framework for priority-based inter vehicle communication for highway safety - Data compression on embedded system - A survey on preserving privacy for sensitive association rules in databases - Boon and bane of curvelet transform Boon and bane of curvelet transform - Security in high performance computing - Trust worthy architecture for mobile Ad Hoc network environment - A cross layer approach for fault management framework in wireless sensor networks - Security solutions to the phishing: transactions based on security questions and image - CloneManager: a tool for detection of Type1 and Type2 code clones - Document image segmentation using recursive top-down approach and region type identification - An analysis to BER performances of differential OFDM systems - MPCS: an account-based secure mobile payment consortia system for educational institutions - Team automata based framework for spatio-temporal RBA - Knowledge discovery in feedback system using pixel oriented technique - Analysis and simulation of a low leakage conventional SRAM memory cell at deep sub-micron level - Enhancing the efficiency of on-demand routing protocol for mobile Ad Hoc networks - Design issues for replacing credit card on mobile phone - Unknown key share attack on STPKE’ protocol - An effective SOA model for developing efficient systems - Refactoring interprocedural dynamic slicing for handling pointers - Image segmentaion and steganography for secured information transmission - Ant system embedded with local search for solving facility layout problem - Strategic initiatives and automated decision support with ERP system environment - A case study of strategic design management - The effects of mannequins on consumers’ perception and shopping attitude - Knowledge transfer: do instructor characteristics matter? - Strong and weak formulations of single stage uncapacitated warehouse location problem - CRM in pharmaceutical sector: meeting the challenges of changing healthcare environment - HR Roadmap: becoming a strategic business partner - Recent trends in Indian technical and management education W.R.T. Maharashtra.